STRATEGI KOMUNIKASI GURU DALAM MENANAMKAN NILAI-NILAI ISLAM DI SD MUHAMMADIYAH TERPADU SENDANG AGUNG LAMPUNG TENGAH - Yulitasari, Iis; Fajar, M. Samson; Islahudin, Ahmad Noor (DECODING: Jurnal Mahasiswa KPI, 2021)
The author gives the title of this thesis "Teacher Communication Strategies In Inculcating Islamic Values in SDMT Sendang Agung Central Lampung" communication strategy is one way that teachers use in instilling Islamic values in everyday life so that a child is accustomed to worshiping without compulsion and burdens such as carrying out the five daily prayers, this type of research is field research (field research) with a descriptive analytical approach. Data collection methods that researchers use are methods of observation, interviews and documentation, data are analyzed by selecting available data, then presented systematically and drawing conclusions. Based on the results of the study, it is concluded that the communication strategy used by the teacher in instilling Islamic values is through communicators (pedagogic and professional competence), communicants (righteousness of aqidah, motivation of worship, and working on amar'maruf nahi mungkar),messages (aqidah, worship and morality). ), media (bil-qoul, bil-amal and bil qudwah hasanah) and effects (increased insight, and implementation in worship) so that as a whole it includes communication strategies related to the cultivation of Islamic values and has been quite successful.